(untitled) (Baghdad Science Journal, 2024)
Duku are endemic plants of Jambi Province, Indonesia. They inhabit and used to grow well in alluvial along riverbanks, but lately have experienced sudden death disease outbreaks for the last decades. This situation has been prevalent since the frequent flooding due to the depletion of forest areas upstream. Since it is caused by water mold Phytophthora palmivora, it was supposed that sudden death disease should only occur in wet areas, but factually, the disease is also found in dry areas. This inspired us to investigate other soil biology factors of its rhizosphere in wet and dry habitats. Samples came from the rhizosphere of diseased and healthy duku in several alluvial areas of the Batang Hari River representing wet and dry habitats. This study found that the soil microbial community in dry and wet habitats was inhabited by mycorrhizal communities, bacteria, and fungi. The relative abundance of microbes in dry and wet habitats in healthy and diseased plants showed varied species. In the wet habitat-healthy plants, the relative abundance of Sclerocytis was 33.33%, Gigaspora 33.34%, and Glomus 33.33%. In the wet habitat-diseased plants, the relative abundance of mycorrhizae was Sclerocytis 66.67%, Glomus 33.33%, and no Gigaspora. The bacteria group was found to be the largest at 70,49% in dry habitats and 72.13% in wet habitats. The fungal group was 14,08% in dry and 16.39% in wet habitats. Mycorrhiza showed the smallest percentage in the rhizosphere of duku plants. We found that VAM correlated negatively with N, and P in the rhizosphere, and Glomus sp. existence correlated positively with soil K.